2021
DOI: 10.3390/rs13132483
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Kobresia pygmaea Community Based on Umanned Aerial Vehicle Technology and Gaofen Remote Sensing Data in Alpine Meadow Grassland: A Case Study in Eastern of Qinghai–Tibetan Plateau

Abstract: The Kobresia pygmaea (KP) community is a key succession stage of alpine meadow degradation on the Qinghai–Tibet Plateau (QTP). However, most of the grassland classification and mapping studies have been performed at the grassland type level. The spatial distribution and impact factors of KP on the QTP are still unclear. In this study, field measurements of the grassland vegetation community in the eastern part of the QTP (Counties of Zeku, Henan and Maqu) from 2015 to 2019 were acquired using unmanned aerial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…A classification method with high universality means that the method obtained in the current study area can be applied to other areas and still achieve promising results. Therefore, it has a higher application value than the methods with low universality [85,86]. Three key parts of the method that significantly affect the final classification results include segmenting the image at the optimal scale, selecting the optimal subset of features, and generating the optimal classification model.…”
Section: The Universality Of the Proposed Methodsmentioning
confidence: 99%
“…A classification method with high universality means that the method obtained in the current study area can be applied to other areas and still achieve promising results. Therefore, it has a higher application value than the methods with low universality [85,86]. Three key parts of the method that significantly affect the final classification results include segmenting the image at the optimal scale, selecting the optimal subset of features, and generating the optimal classification model.…”
Section: The Universality Of the Proposed Methodsmentioning
confidence: 99%
“…Combined with relevant research progress at home and abroad, it can be seen that multirotor UAVs are the most commonly used types [8], mainly including quad-rotor, hexa-rotor and octo-rotor UAVs, among which octo-rotor UAVs are the most widely used. The overall payload of the UAV ranges from 2.5 kg to 6.0 kg, with a maximum payload of 50 kg [23,[27][28][29][30][31]. The flight altitude of UAVs varies from 10 to 100 meters, and some scholars have studied the impact of flight altitude on modelling accuracy [32,33].…”
Section: Uav Platforms and Sensorsmentioning
confidence: 99%
“…The results showed that the images obtained by UAV remote sensing technology had high spatial resolution, and the overall accuracy of species classification was approximately 85%, which could provide a reference method for relevant studies [23]. Meng et al constructed a machine learning algorithm for grassland vegetation community classification by using UAV technology and combining high-resolution satellite images and topographic indices in alpine meadows of the Qinghai-Tibet Plateau and achieved spatial mapping of the Kobresia pygmaea community [27].…”
Section: Vegetation Species Surveymentioning
confidence: 99%
“…On the other hand, the FragMap system realized a repeated and long term monitoring (Yi, 2017), i.e., For each set of way points of GRID route, multiple flights with fixed height (20 m) could be executed at different times to conduct repeated monitoring of NDVI. Combined with BELT route (2 m), species monitoring is possible (Sun et al, 2018a;Wei et al, 2020;Meng et al, 2021). In our future studies, we will monitor dynamic changes in species and their NDVI over long-term period and over large regions, including the desert steppe, typical steppe, and the transition zone, to reveal the mechanism of the asymmetric response of ANPP to precipitation using a UAV.…”
Section: Mechanism Of Anpp Asymmetric Response To Precipitation Requi...mentioning
confidence: 99%